The Relationship Of Breast Care During Antenatal Care With The Following Of Breast Milk In Breastfeeding Mothers In The Clinic Self Practice Of Indah Suryawati Midwifery BinjaiTimur Binjai City 2020 - Tarigan, Nanarita (Jurnal Kesehatan Langkat Berseri (JURKESLASER), 2021)
Breast care is a necessity for mothers who have just given birth and a very important action to facilitate the release of breast milk. Breast care, often called Breast Care, aims to maintain breast hygiene, increase or facilitate the release of breast milk so that there is difficulty in breastfeeding the baby. Breast care is done by massage. Expenditure of breast milk is said to be smooth if excessive milk production is marked by the milk will drip and will radiate profusely when sucked by the baby. The type of research used is a chis-square test with a cross-sectional study design. Sampling was carried out by Total Sampling with a total of 30 people. In sampling, inclusion and exclusion criteria are needed to reduce the risk of bias. Based on the results of the chi-square test (p.value) showing the chi-square count which is smaller than the chi-square table, it can be concluded that Ho is rejected and Ha is accepted at a 5% significance level. So there is a relationship between breast care during antenatal care on smooth breastfeeding in breastfeeding mothers at the Kuala Subdistrict Clinic, which is significant with a significance level of (Î¬) 5% degrees of freedom (df) 2 and n=30. It is recommended to the public, especially pregnant and lactating women, to carry out breast care to increase the smooth flow of breast milk and to follow counseling and advice from health workers.